Preacher as Communicator: The Role and Credibility in Delivering Da'wah to the Converted Community in the Karomba Mountains Area, Pinrang Regency - Aswar Tahir; Hafied Cangara; Arianto Arianto (BBPSDMP KOMINFO MAKASSAR, 2021)
This study aims to analyze the role and credibility of preachers as communicators in conveying the message of da'wah to the converted community in the Karomba Mountain Area Pinrang Regency. This research uses qualitative methods to understand and analyze the role and credibility of preachers in conveying the message of da'wah. data collection techniques are carried out with in-depth interviews, direct observations, and documentation. Data analysis techniques in this research are data reduction, data presentation, and conclusion drawing. The results of this study found that the role of preachers in conveying the message of da'wah to the converts, namely preachers as mentors or coaches. preacher as an extension of Islam and preacher as the problem solver. While the credibility of preachers as communicators in conveying the message of da'wah can be seen from communication skills, knowledge related to the values of Islamic religious teachings, attitudes, and socio-cultural systems.